PROSPECTS OF THE DEVELOPMENT OF THE LEATHER INDUSTRY IN UZBEKISTAN (Marketing Journal, 2025)
This article discusses the current issues, current opportunities and prospects for the development of the leather industry in the Republic of Uzbekistan. Increasing the contribution to the national economy through leather processing, production of finished products and increasing export potential is of great importance. Also, promising areas for attracting foreign investment in the leather industry, developing local brands and filling the domestic market are indicated.
Keywords: agriculture; leather and footwear production; technology; export; diversification; logistics; infrastructure; marketing